Invasive brown widow spiders disperse aerially under a broad range of environmental conditions. (12th June 2022) - Mowery, Monica A.; Lubin, Yael; Segoli, Michal
Abstract: Spiders commonly disperse on silk lines as juveniles by means of rappelling or ballooning. These modes of dispersal, especially long‐distance dispersal via ballooning, can greatly increase the distance an individual can move and, at the population level, the speed of range expansion and likelihood of gene flow. Nevertheless, few studies have examined how spiders disperse under field conditions, and which environmental and meteorological conditions may affect their decision to disperse. We tested dispersal by spiderlings of the invasive brown widow ( Latrodectus geometricus ) under field conditions in the Negev Desert of Israel. We documented pre‐dispersal (climbing and tiptoeing) and dispersal (short‐distance dispersal by rappelling and long‐distance dispersal by ballooning) behaviours during the day ( n = 147 spiders) and night ( n = 171 spiders), while recording wind speed, temperature and humidity. We found that spiders ballooned significantly more during the day (14.3%) compared with 1.8% of spiders ballooning at night. At night, spiders were more likely to disperse in conditions of higher wind speeds, lower temperature and higher humidity, whereas during the day, environmental factors were less predictive of dispersal behaviour. In addition, we found significant differences in the proportion of spiderlings showing pre‐dispersal and dispersal behaviour depending on family line. In conjunction with human‐mediated dispersal, ballooning and rappelling may be an important mechanism of range expansion in the brown widow spider. Understanding the environmental and genetic factors affecting dispersal may lead to better management of invasive species. Abstract : We tested dispersal by spiderlings of the invasive brown widow ( Latrodectus geometricus ) under field conditions in the Negev Desert of Israel. Invasive brown widow spiderlings ballooned more during the day than at night and under a wide range of environmental conditions. Understanding which factors promote dispersal of this species, especially long‐distance dispersal such as ballooning, can help predict and manage the species' invasion success.